2022
DOI: 10.1098/rsos.210520
|View full text |Cite
|
Sign up to set email alerts
|

A bioenergetics approach to understanding sex differences in the foraging behaviour of a sexually monomorphic species

Abstract: Many animals show sexually divergent foraging behaviours reflecting different physiological constraints or energetic needs. We used a bioenergetics approach to examine sex differences in foraging behaviour of the sexually monomorphic northern gannet. We derived a relationship between dynamic body acceleration and energy expenditure to quantify the energetic cost of prey capture attempts (plunge dives). Fourteen gannets were tracked using GPS, time depth recorders (TDR) and accelerometers. All plunge dives in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 100 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Differences in foraging performance between sexes are common in mammals and birds and are often due to differences in body size and parental duties (Lewis et al, 2002 ), In monomorphic species such as the Griffon Vulture, these differences might be associated with energetic and nutritional requirements for reproduction (Bennison et al, 2022 ; Pinet et al, 2012 ). Our results showed that females have larger home‐ranges and travel farther than males.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in foraging performance between sexes are common in mammals and birds and are often due to differences in body size and parental duties (Lewis et al, 2002 ), In monomorphic species such as the Griffon Vulture, these differences might be associated with energetic and nutritional requirements for reproduction (Bennison et al, 2022 ; Pinet et al, 2012 ). Our results showed that females have larger home‐ranges and travel farther than males.…”
Section: Discussionmentioning
confidence: 99%
“…Using an approach based on accelerometer sensors, ecologists will be increasingly able to remotely and continuously estimate specific behaviours of wild animals and how they may vary among individuals (Bidder et al . 2020; Bennison et al . 2022) and over time (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…vigilance (Benhaiem et al 2008;Favreau et al 2014)), usually during the day and in habitats that provide high observability. Using an approach based on accelerometer sensors, ecologists will be increasingly able to remotely and continuously estimate specific behaviours of wild animals and how they may vary among individuals (Bidder et al 2020;Bennison et al 2022) and over time (e.g. according time of day and season (Hammond et al 2016;Rast et al 2020), according to environmental conditions).…”
Section: Inferring the Circadian Time Budget Of Free-ranging Animalsmentioning
confidence: 99%
“…Dives were identified from accelerometry using threshold analysis [37,38]. Dives occurred when average acceleration (running average of 2 s) in the x-axis was less than 0 g and standard deviation in the mean x-axis was greater than 1.4 g following Bennison et al [39]. Roll was calculated as the rotation of the individual in the x-axis and is calculated using the following formula:Roll=(true0yx2+ z2) × (true0180π)where x is the acceleration in the forward-facing surge channel, y is the acceleration in the lateral sway channel, and z represents the acceleration in the vertical heave channel.…”
Section: Methodsmentioning
confidence: 99%
“…Dives were identified from accelerometry using threshold analysis [37,38]. Dives occurred when average acceleration (running average of 2 s) in the x-axis was less than 0 g and standard deviation in the mean x-axis was greater than 1.4 g following Bennison et al [39]. Roll was calculated as the rotation of the individual in the x-axis and is calculated using the following formula:…”
Section: (B) Data Processing and Behaviour Classificationmentioning
confidence: 99%